Knowledge, Attitude and Practice of Type 2 Diabetic Patients Visiting Diabetic OPD of TUTH and Non Diabetic Population of Kathmand - Sapkota, Yogita (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Introduction: Diabetes Mellitus is a major lifestyle disorder disease which is further expanded due to ignorance and lack of knowledge. This study was carried out to assess the Knowledge(K), Attitude (A) and Practice (P)-KAP among diabetic patients visiting diabetic OPD of Tribhuvan University Teaching Hospital (TUTH) and nondiabetic population residing in Kathmandu, Nepal and compare KAP with each other’s. Methods: A cross-sectional survey design was used to assess KAP of both 90 diabetic and 90 non-diabetic population and associated factors via interview administered Questionnaire. Results: Among diabetic population, it was found that, the mean±SD Knowledge, Attitude and Practice score was 12.97±5.682, 3.28±1.805 and 11.87±4.604 respectively.60%, 70% and 47.8% of diabetic participants had good knowledge, attitude and practice scores respectively. A significant association was found between KAP score and education level of the patient and with Physical Activity level of the patient. No significant association was found between KAP score and Age group and with genetic history of the patient. Among non-diabetic population, it was found that, the mean±SD Knowledge, Attitude and Practice score was 10.89±4.496, 3.31±1.605 and 7.46±3.098 respectively. 40%, 73.3%and 51.1% of the non-diabetic participants had good knowledge, attitude and practice scores respectively. Significant difference between the mean knowledge score of diabetic and non-diabetic group (P<0.05, P=0.007) was found but no significant difference between the mean attitude score of diabetic and non-diabetic group (P>0.05, P=0.896) was found. Conclusions: Overall, this study revealed good knowledge, good attitude but poor practice among diabetic group. In contrary poor knowledge but good attitude and poor lifestyle practices was found among non-diabetic group. Therefore, need based awareness programs and educational interventions targeting both diabetic and non-diabetic population should be developed and launched. Jour of Diab and Endo Assoc of Nepal 2018; 2 (1): 17-23